Information Technology System dan Self Esteem Sebagai Solusi Pembelajaran Islam Kontemporer di Era Globalisasi - Syahbana, Rabian (Tarbawy : Jurnal Pendidikan Islam, 2021)
life. Thanks to the development of the technology is growing very rapidly, especially the technology of computer equipment and telecomunications equipment technology. Information and communication technology is a key enabler of globalization. Technology systems and confidence have interlocking relationships between one another. Because the current information technology is a very important that human need, because it is one way for people to get to know themselves and the world outside themselves in the face of gobalization. Contemporary Islam as a begining and creative work to create a new Islamic tradition after the Muslims suffered defeat in the political struggle. Excepted with the capabilities of information technology and self-esteem a person is able to convery ideas, ideas and knowledge of the religion of Islam to others. Information technology systems and self-esteem become a necessity in applying contemporary Islamic religious learning era of gobalization. Development of information technology systems that always moves must be followed and offset by Muslims to remain a quality human. Muslims are required to be able use information technology as well as possible so as to have high confidence in the study of the Islamic religion in the current era of globalization.